Budaya Kopi Global dan Perubahan Gaya Hidup Perkotaan di Makkah - Hutama, Lanang (Jurnal ICMES, 2025)
This study examines the shift in coffee consumption culture in Saudi Arabia as a result of cultural globalization, with a focus on the younger generation around Masjid al-Haram and Masjid al-Nabawi. Arabic coffee (qahwa), which was previously rooted in family and assembly traditions, is now undergoing a transformation into a part of urban lifestyle and symbolic consumption. This phenomenon is reflected in the emergence of modern coffee shops such as Ratio and Moment Coffee which function as new social spaces in religious areas. This research uses a qualitative approach with case studies, supported by the theories of cultural globalization, globalization, and symbolic consumption. Data were obtained through participatory observation and interviews with coffee shop visitors. The findings of the study show that coffee consumption transforms into a medium for negotiating the identity, modernity, and cosmopolitan aspirations of the younger generation, without completely eliminating local cultural references. Local values have not vanished, but are reinterpreted and contextualized in modern consumption practices, thus creating a hybrid cultural space between tradition and globalization in the daily lives of Saudi people.